Capturing CO2 Emissions in the Iron Industries using a Magnetite–Iron Mixture. Issue 5 (16th February 2016) - Kumar, Sushant; Drozd, Vadym; Durygin, Andriy; Saxena, Surendra K.
Abstract: We examined a mixture of magnetite (Fe3 O4 ) and iron (Fe) as a possible CO2 sorbent easily applicable for any ironmaking industries. The mixture reacts with CO2 to form siderite (FeCO3 ). Our experimental results illustrate a capture capacity of 7.98 mmol CO 2 g - 1 sorbent for the reactant mixture at 200 °C and 10 bar CO2 pressure in 3 h. The results also show that the kinetics of the carbonation reaction vastly depend on the applied temperature and CO2 pressure. The magnetite was completely regenerated by heating siderite at 350 °C under air flow. The proposed set of reactions can be integrated at any ironmaking sites and can provide a potential solution for CO2 capture in the future. Abstract : No waste : A method is proposed to capture CO2 at iron and steel industries using a mixture of iron and magnetite. Both these materials are readily accessible at any ironmaking sites and can selectively combine with the CO2 gas present in blast furnace gas to form siderite. Unreacted raw materials can then be magnetically separated from siderite, which can be decomposed to generate magnetite and pure CO2 gas to regenerate the process.